Application Of Warm Cinnamon Compres Theraphy For Gouty Arthritis To Reduce Pain In The Elderly Through The Ida Jean Orlando - Yunita, Yuyun; Handayani, Tita Septi (Universitas Dehasen Bengkulu, 2025)
Gout Arthritis is a disease characterized by joint pain that suddenly recurs due to the deposition of monosodium urate crystals that accumulate in the joints as a result of high levels of uric acid in the blood (hyperuricemia). Usually known as gout (Elfira, 2020).The aim of this research is to understand and apply nursing care to reduce pain in Gouty Arthritis sufferers by applying Hangta Kay Manis compress therapy through the Ida Jean Orlando application in the Small Bridge Health Center Work Area, Bengkulu City in 2024. The method for writing this Final Scientific Work is in the form of a case study with 2 subjects suffering from Gour Arthritis with pain who were taken in the work area of ​​the Jembatan Kecil Health Center, Bengkulu City and provided nursing care for 3 days.The results obtained after implementing warm cinnamon compresses on Mrs.It was concluded that there was a significant effect of applying warm cinnamon compresses on reducing pain in sufferers of Gouty Arthritis. After carrying out this case study, it is hoped that clients will feel the benefits and can use it as an alternative non-pharmacological therapy to help reduce the scale of pain in sufferers of Gouty Arthritis.